Awal mula kaum Jabariyah dan Qodariyah - Bahar, Athoillah (Maliki Interdisciplinary Journal, 2025)
This article examines the historical emergence of two influential theological schools within Islam, namely Jabariyyah and Qadariyyah, which center on debates concerning divine predestination and human free will. Jabariyyah, pioneered by Jahm ibn Safwān, teaches that humans possess no free will, as all events occur solely by God’s absolute decree. In contrast, Qadariyyah initiated by Ma‘bad al-Juhani and Ghaylan al-Dimashqi emphasizes human freedom in making choices and bearing responsibility for their actions. This study outlines the historical background of both schools, their intellectual methodologies, and their impact on the development of Islamic theology. It also explores the critiques directed at each school and highlights how their ideas have shaped theological debates among Muslims.